Use of film as didactic tool - Hornjak, Sonja N. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
Due to the fact that film can be efficient resource in teaching the Spanish language if it is applied in a right way, we analyzed the organization of class of the Spanish language with а film. Working with film means a serious organization in a didactical sense. The organization of a class with the film presents a multilayerd process which has few phases, from the preparatory phase to realization phase, whereby various criteria should be kept in mind. In this paper we also illustrated the example of accompanying activities for the class of Spanish language with а film. The purpose of the paper is to bring this topic closer to teachers and to give them guidelines and support for its application.